Demokrasi dalam Islam: Suatu Pendekatan Tematik Normatif Tentang Kepemimpinan Perempuan - Murniyetti, Murniyetti (Pusat Kajian Civics Fakultas Ilmu-ilmu Sosial Universitas Negeri Padang, 2005)
This research start from a question, is there opportunity for woman to be chief executive, if its coorelated with the prohibition to women’s leadership according to Islamic law?. Beside, how to understand claim from people about equality of man and woman in every things. Result of this research can be concluded that there is khilafiyah (different opinions) in determine of law of the womanas achief executive. Ulama classic didn’t permite woman as chief executive by understanding texs al-Qur’an verses, hadis and ijmak. Meanwhile, ulama contemporer permited woman to be a leader by understanding verses of Qur’an and hadis by understanding contexs; looking social conditions, histories and facts which been. The writer conclude by combine both of opinions (understanding text and context) by applying the texs of verses before, but those verses can be understood by contextual. Kata Kunci: Demokrasi, Kepemimpinan, Islam, gender, perempuan